RANCANG BANGUN PERBAIKAN FAKTOR DAYA MENGGUNAKAN KAPASITOR BANK BERBASIS MIKROKONTROLER UNTUK BEBAN RUMAH TANGGA DENGAN DAYA MAKSIMAL 900 W - Reza Ramadhan; Surojo Surojo; Zanu Saputra (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
In the current global climate, humans will feel a big impact, especially in terms of energy. We must be more efficient in the use of energy, especially in the use of electrical energy. In Indonesia itself, household goods and equipment that are often used are generally inductive in nature. This inductive nature makes the use of electrical energy more wasteful and less efficient. The purpose of this research is to design a control system to improve the power factor of household loads using a capacitor bank. When the load is operating, the current, voltage, and power factor values ​​will be read by the sensor which is then sent to the microcontroller. After the cos phi value is known, the microcontroller will process the control program and give a command to the relay module to activate the capacitor bank. After activating the capacitor, the sensor reads the current, voltage, and power factor values ​​again to determine the change in cos phi until it reaches the desired cos phi value. Based on the test results on 4 types of loads that were measured cumulatively, the average initial power factor value of 0.74 rose to the ideal power factor value of 0.95.